Inventarisasi dan identifikasi makroalga di Perairan Talawaan Bajo, Sulawesi Utara - Rajagukguk, Bulfrit B.; Kambey, Rama Presley; Opa, Samuel Leivy; Pamikiran, Vivi Aganitji; Rumengan, Roles; Sumolang , Cakra Sigar (Universitas Sam Ratulangi, 2023)
Macroalgae have ecological and economic benefits both directly and indirectly, so they have great potential to be developed. This study aimed to determine the types, abundance and diversity of macroalgae in the coastal waters of Talawaan Bajo. Sampling used the line transect method with a quadratic sampling technique. The data that had been collected was analyzed used descriptive statistical analysis. There were 21 species of macroalgae consisted of Chlorophyta six species (29%), Rhodophyta twelve species (57%), and Phaeophyta three species (14%). The highest density was found in the class Rhodophyta. There were no dominating species and the uniformity value was high and in stable condition. The diversity index was classified as moderate. Research result showed that environmental factors in Talawaan Bajo Waters were favorable for macroalgae growth. Keywords: Structure community, Rhodophyta, Chlorophyta, Phaeophyta, biodiversity